Vendetta [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2018)
With his dying breath, Carl Venable, head of the CIA task force on terrorism and Jude Brandon's final link to terrorist ringleader Max Huber, gives Brandon a mandate: to keep his daughter, Rachel, safe at any cost. But Rachel Venable has a shocking, twisted past of her own, one that comes rushing back after her medical clinic in Guyana is attacked by Huber - the same man who murdered her father and kept her imprisoned for months. Brandon and Catherine Ling, Rachel's longtime ally and fierce protector, are determined to keep Rachel out of danger, but she knows that it's impossible to stay hidden when Max Huber wants you dead. As Rachel and Brandon race against the clock to bring Huber down before he can orchestrate a nuclear explosion that will lay waste to the west coast, they also fight a growing attraction to each other - an attraction that could prove just as dangerous as Huber himself.